2015
DOI: 10.1111/jgh.12863
|View full text |Cite
|
Sign up to set email alerts
|

Statewide hepatitis C model of care for rural and remote regions

Abstract: The evolution of management of hepatitis C virus (HCV) has seen a majority of patients treated being regarded as cured. Despite this development, uptake of treatment remains low in Australia, and this is particularly true in rural and remote areas. The largest state in Australia, Western Australia (WA), covers an area of 2500 km 2 . As the rural and remote population of WA is scattered in small areas rather than major centers, poor accessibility to remote areas and lack of adequate of medical and nursing resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Telehealth was considered highly effective and a viable option when supported by appropriately trained health professionals and clear treatment protocols. This finding was consistent with another WA study [ 22 ] and the findings of Project ECHO (Extension for Community Healthcare Outcomes) which found treatment of HCV patients at 21 rural ECHO sites and prisons in New Mexico using telehealth to be comparable to treatment of patients at an HCV clinic in reaching a sustained virological response [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…Telehealth was considered highly effective and a viable option when supported by appropriately trained health professionals and clear treatment protocols. This finding was consistent with another WA study [ 22 ] and the findings of Project ECHO (Extension for Community Healthcare Outcomes) which found treatment of HCV patients at 21 rural ECHO sites and prisons in New Mexico using telehealth to be comparable to treatment of patients at an HCV clinic in reaching a sustained virological response [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…Liver disease also contributed to aeromedical retrievals for GI disorders (3.6%; n = 217). This finding is consistent with research that indicates that rural and remote populations have higher rates of untreated hepatitis C and increased prevalence of excessive alcohol consumption, both of which are linked to liver cirrhosis and cancer . This, coupled with the increasing rates of substance use disorders requiring aeromedical retrieval, indicates a complex clinical environment …”
Section: Discussionsupporting
confidence: 89%
“…Some local health districts in New Zealand have implemented incentives for GPs who provide HCV treatment in a primary care setting, 20 and in Australia this strategy is being used on an ad hoc basis for some patient groups. Models of care using nurse practitioners upskilled in the treatment of HCV and telehealth services supported by specialists may help improve treatment rates, particularly in remote areas with limited access to GP or specialist services 21,22 . Findings of a recent study from South Australia showed that models of care that include GPs or mixed consultant nurse models are cost‐effective ways of promoting HCV treatment uptake 23 .…”
Section: Discussionmentioning
confidence: 99%